Characterization of Biogas-Syngas Turbulent MILD ‎Combustion in the Jet in Hot Co-Flow Burner - O. Benbouaziz (Isfahan University of Technology, 2021)
Moderate or Intense Low–oxygen Diluted (MILD) combustion is a promising technology with interesting ‎properties such as high efficiency and zero-emission. The biogas-syngas mixture is also considered a ‎promising new renewable biofuel with low emissions. This work aims to examine the effects of several ‎parameters on the biogas-syngas flame structure and emissions under MILD conditions in the Jet in Hot ‎Co flow (JHC) burner. The turbulence is modeled by the modified standard k-ε model; whereas ‎combustion-turbulence interaction is handled by the Eddy Dissipation Concept (EDC) in conjunction with ‎three detailed reaction mechanisms, namely: GRI-Mech 3.0, GRI-Mech 2.11, and DRM 2.11. Effects of ‎biogas-syngas composition, temperature, and oxygen concentration in the hot co-flow and Reynolds ‎number of the fuel jet have been elucidated. Results show that flame structure is more sensitive to the ‎increase of hydrogen in syngas than that of methane in biogas. An increase of oxygen concentration or ‎temperature in the co-flow stream leads to more NO formation whereas Reynolds number augmentation ‎reduced them. Furthermore, NO species production is globally governed by the NNH route‎‎.